Significant Insights into the Origins of Reaction Barriers Governing the Addition Reactions of Olefins with Singly Bonded G13/P-Based (G13=Group 13 Element) and Al/G15-Based (G15=Group 15 Element) Molecules - Wu, Shi-Hao; Su, Ming-Der (Chemistry, an Asian journal, 2025)
The addition reactions of propylene with singly bonded G13/P-based (G13=Group 13 element) and B/G15-based (G15=Group 15 element) molecules, all yielding the >G13-G15< geometrical structure, have been analyzed theoretically using density functional theory (DFT). The current DFT findings indicate that, of all singly bonded G13/P-based and Al/G15-based molecules, only Al/P-Rea can reversibly carry out the [2+2] addition reaction with propylene, both from kinetic and thermodynamic viewpoints. The activation strain model suggests that the deformation energy of the singly bonded >G13-G15< fragment is pivotal in determining the barrier heights that allow for optimal orbital interactions between G13/P-Rea, Al/G15-Rea, and propylene. Our theoretical analyses demonstrates that donor-acceptor bonding (singlet-singlet) has a greater impact compared to electron-sharing bonding (triplet-triplet) in the transition states G13/P-TS and Al/G15-TS. Sophisticated analytical frameworks suggest that the forward interaction (lone pair (G15)→p-π* of C=C in propylene) predominantly affects the addition reactions of singly bonded G13/P-Rea and Al/G15-Rea with propylene, whereas the backward interaction (p-π*(G13) ← p-π of C=C in propylene) is less influential. Our current DFT calculations, focusing on the structures and relative energetics of stationary points analyzed through the earlier mentioned advanced methods, conform to the Hammond postulate.